2016
DOI: 10.1371/journal.pone.0153584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phytoecdysteroids (PEDS) Extracted from Cyanotis arachnoidea on Rumen Fermentation, Enzyme Activity and Microbial Efficiency in a Continuous-Culture System

Abstract: The objective of this study was to evaluate the effects of supplementation of phytoecdysteroids (PEDS) extracted from Cyanotis arachnoidea on rumen fermentation, enzymes activity and microbial efficiency in a dual flow continuous-culture system. A single-factor experimental design was used with twelve fermenters in 4 groups with 3 replicates each. Fermenters were incubated for a total of 7 days that included first 4 days for adaptation and last 3 days for sampling. PEDS was added at levels of zero (as control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Complex rumen microbial communities play important roles in absorption in the host [ 40 ], and their compositions are influenced by diets [ 53 ]. The present study revealed the presence of a strong core microbiome among three feed type groups (approximately 69% of total OTUs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex rumen microbial communities play important roles in absorption in the host [ 40 ], and their compositions are influenced by diets [ 53 ]. The present study revealed the presence of a strong core microbiome among three feed type groups (approximately 69% of total OTUs).…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of the reaction solutions was measured at 540 nm. One enzyme activity unit (U) was defined as the amount of glucose (μmol) produced by 1 mL of enzyme in one minute (μmol/min·mL) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Os ruminantes caracterizam-se por apresentar sistema digestório especializado no processo de fermentação, sendo capazes de digerir diferentes tipos de forragens, graças a interação evolutiva que desenvolveram com os microrganismos, sendo essa interação benéfica para o hospedeiro e para a microbiota (Li et al, 2016).…”
Section: Integração Do Metabolismo Microbiano E Metanogênese Em Ruminunclassified
“…A utilização de extratos vegetais como alternativa na manipulação ruminal, favorecendo da utilização de energia em ruminantes, tem sido reportado na literatura científica. A adição desses extratos pode ter efeitos deletérios na microbiota ruminal produtora de H2, alterando o processo de fermentação ruminal e favorecendo a produção de propionato, que irá aprimorar a eficiência no uso da energia dos alimentos (Piñeiro Vázquez et al, 2015;Li et al, 2016).…”
Section: Relação Microbiana E Redução Do Metano Em Ruminantesunclassified
“…Rumen microbiota plays a pivotal role in feed digestion and acts synergistically to degrade plant structural and non-structural carbohydrates into volatile fatty acids (VFAs) and microbial proteins (MCP) ( 7 ). The end products of rumen fermentation (VFA) are used as the substrate for fueling other animal tissues (including liver, fat, and muscle) and MCP are required by the host to produce meat and milk ( 8 ). The change of rumen bacterial community structure was reported to be closely related to the composition of the diet ( 9 ).…”
Section: Introductionmentioning
confidence: 99%